The Development of creative thinking and problem-solving skill instrument of plant growth in high school - Bernadetta Ersi Purwandari; S Supriyatin; Rizhal Hendi Ristanto (Universitas Negeri Jakarta, 2022)
Creative thinking and problem-solving skills are needed to face the 21st century of 4.0 industrial revolution. Improving the quality of human resources to face the era of the industrial revolution 4.0 must be developed in education. Biology as one of the subjects in high school, especially in plant growth and development matters, allows to develop creative thinking and problem-solving skills because in it there is a student project on plant growth and development. It takes the right instrument to measure the achievement of creative thinking skills and problem solving skills in Biology learning, especially on the topic of plant growth and development. Two instrument questions have been developed, namely the instrument for creative thinking skills and problem solving skills. The development of this instrument was carried out through the stages of Research and Development Borg and Gall 1983. It produced 10 essay questions measuring creative thinking skills and 8 questions measuring problem solving skills. The question gets very decent expert validation criteria with a score of 91% - 97%. The results of the validation test based on the Pearson Product Moment formula show that the ten items of creative thinking skills are valid with a significance level of 0.05. The reliability test of the two instruments has a result of 0.82, above Cronbach's Alpha coefficient, which is reliable for creative thinking skills instruments. Meanwhile, the instrument of problem solving skills showed very reliable results with Cronbach's Alpha value of 0.95.